ISSUES OF DEVELOPING KNOWLEDGE OF THE SPORT IDEAL IN THE PHYSICAL EDUCATION PROCESS - Rustamova, Feruzakhon Makhmudjanovna (Oriental Journal of Education, 2026)
The article examines the essence of the contextual approach and systematic methods of interconnected activities between the teacher and students. These methods are aimed at achieving the goals of education, upbringing, and personal development within the process of teaching Russian as a Foreign Language (RFL) to students in Oriental studies at philological universities.